Implications of Quota Reallocation in the Torres Strait Tropical Rock Lobster Fishery. (3rd May 2013) - Pascoe, Sean; Hutton, Trevor; van, Ingrid; Dennis, Darren; Plaganyi‐Lloyd, Eva; Deng, Roy
<x xml:space="preserve">Abstract</x> The Torres Strait Tropical Rock Lobster Fishery is exploited by a mix of Islander and non‐Islander fishers. While the former group dominates in terms of numbers of fishers, a disproportionate share of the nominal quota is held by the substantially smaller non‐Islander fleet. In 2011, the nominal quota allocation was 54:46 between Islanders and non‐Islander, with the Islander share increasing substantially since 2005 through a buy‐back of around half the non‐Islander fleet. Despite this increase, there is pressure within the Islander communities to further increase their share of the total quota. In this paper, we consider the relative value of a unit of quota to the Islander and non‐Islander fleets and the likely impact this will have on potential quota trade. We estimate production frontiers for the two groups of vessels to derive estimates of the marginal value product of the different fleet segments. From this, we determine if there are efficiency arguments for transferring additional quota to the Islander fleet. We conclude that economic incentives for individual Islanders to purchase quota from non‐Islanders are limited, and that some other form of reallocation system may be more successful in achieving the objective of an increased quota share to Islanders.